2016
DOI: 10.1186/s12890-016-0228-y
|View full text |Cite
|
Sign up to set email alerts
|

Design of a prospective, multicenter, global, cohort study of electromagnetic navigation bronchoscopy

Abstract: BackgroundElectromagnetic navigation bronchoscopy (ENB) procedures allow physicians to access peripheral lung lesions beyond the reach of conventional bronchoscopy. However, published research is primarily limited to small, single-center studies using previous-generation ENB software. The impact of user experience, patient factors, and lesion/procedural characteristics remains largely unexplored in a large, multicenter study.Methods/DesignNAVIGATE (Clinical Evaluation of superDimension™ Navigation System for E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 47 publications
0
44
0
1
Order By: Relevance
“…Not applicable to patients with a diagnosis of cancer that has been made within the previous 5 years or to patients with previous lung cancer [29] b See Folch et al 2016 for definitions [7]…”
Section: Resultsmentioning
confidence: 99%
“…Not applicable to patients with a diagnosis of cancer that has been made within the previous 5 years or to patients with previous lung cancer [29] b See Folch et al 2016 for definitions [7]…”
Section: Resultsmentioning
confidence: 99%
“…This new technology has been successfully used on animal models since 2003; the first human study was performed in 2005; and to date, over 20,000 procedures have been performed (4,11). During the procedure, ENB-aided diagnostics yielded approximately 75% accuracy and the occurrence of pneumothorax was less than 5% in most studies (12). Thus far, it has become a most suitable assessment tool for SPPLs.…”
Section: Discussionmentioning
confidence: 99%
“…To answer this question, we designed this study following previously reported instructions (12). Three physicians from our hospital have been using ENB since 2013.…”
Section: Discussionmentioning
confidence: 99%
“…NAVIGATE (http://www.clinicaltrials.gov, NCT02410837) is a prospective, multicentre, global, and single‐arm cohort study evaluating ENB procedures . All ENB procedures used the superDimension navigation system version 6.0 or higher (Medtronic, Minneapolis, MN).…”
Section: Methodsmentioning
confidence: 99%